Identification, characterization and antibiotic susceptibility testing for Bacillus species - Noha Alaa Eldin Fahim; Ghada Abd El-Wahed Ismail; Moataz Bellah Abdelaleem; Mervat Elanany; Sally Mohamed Saber; Marwa Abd EL-Rasoul EL-Ashry (Iranian Journal of Microbiology, 2022)
Background and Objectives: With the increase in immunosuppressed patients and antimicrobial misuse, Bacillus species have risen as opportunistic pathogens in hospitalized patients. The present study aimed at comparing chromogenic media, automated identification cards versus MALDI-TOF as the gold standard method for identification of different Bacillus species and determining minimal inhibitory concentration (MIC) of different antibiotics by broth microdilution method (BMD) to suggest recommendations for Bacillus treatment. Materials and Methods: The study included 30 Bacillus species isolates recovered from normally sterile sites of the human body and were subjected to identification by MALDI-TOF, Vitek-2c, and HiCrome Bacillus Agar. BMD test was performed to determine the MIC of vancomycin, gentamicin, and ciprofloxacin. Results: Our study showed B. cereus was the most commonly isolated species (76.66%) followed by B. subtilis (23.33%). Regarding the different methods of identification, the highest agreement with MALDI-TOF was exhibited by HiCrome agar without polymyxin B (93.3%) followed by Vitek-2C and HiCrome agar with polymyxin with an agreement of 83.3%. Concerning the antibiogram, the tested isolates showed a susceptibility of 93.3%, 86.6%, and 83.3% towards vancomycin, gentamicin, and ciprofloxacin respectively. Conclusion: In conclusion, we spotlight that Bacillus species should no longer be considered contaminant bacteria in cultures, particularly in immunosuppressed patients. HiCrome Bacillus Agar without polymyxin B displayed the highest agreement with MALDI-TOF. Hence, it represents a good option for identification for routine laboratories where expensive instruments are unavailable. The high susceptibility towards the tested antibiotics can suggest the possibility of empirical use of vancomycin, gentamicin, and ciprofloxacin.